Deranged Liver Enzymes in COVID-19 Patients; and its Impacts on Prognosis - Asif Islam, Malik M. Atif, Summaya Shabbir, Samara Siddique, Tooba Fatima, Bilal Aziz, Yasir Imran, Zainab Younus, Bilquis Shabir, (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: The objective of this study was to investigate derangement of liver enzymes in COVID-19 patients. The prevalence of deranged hepatic enzymes with COVID-19 infection, its association with other co-morbidities and any changes in its prognosis were investigated. Methodology: This study was conducted in Mayo hospital from 1st June 2021 till 31st September 2021. A number of 224 patients were included in this study. Both male and female patients of varying age groups were included in the study. Laboratory tests were conducted to collect data related to liver enzyme values of each patient. Liver function test (LFT) was performed twice, first on day 1 and then on day 7 to observe any further changes in liver enzymes values in COVID-19 patients. The LFTs of the patients told us Bilirubin, Alanine aminotransferase (ALT), Alkaline Phosphatase (ALP), C-reactive protein (CRP), Ferritin and D-dimer levels in the body. The data were analyzed by SPSS analysis. The t-test used was for the comparison of standard features in both groups. The P value less than 0.05 was regarded significant. Data about co-morbidities, autoimmune disease and its treatment, and outcome was also collected. Gender, autoimmune disease and COVID-19 PCR data was analyzed using descriptive analysis. Prevalence of deranged liver enzymes in COVID-19 patients was analyzed using paired sample test. Association with co-morbidities and prognosis was also analyzed by frequency analysis. Results: Sample consists of 224 individuals among them the ratio of male and female was 50:50 with age ranging 17-90 years. There were 220 COVID-19 PCR positive patients, 1 negative and 3 suspected patients with about 89.7 per cent patients having no autoimmune disease. The results showed that bilirubin, ALT and D-dimer show significant derangement in COVID-19 patients while ALP, CRP and Ferritin did not. The patients with both diabetes mellitus and hypertension showed the highest percentage of association with the value being 25 percent. Other co-morbidities like asthma, chronic liver disease and hepatitis C among many other also showed association with corona virus disease. And the results of prognosis showed that 33 percent, of the patients were shifted to the ICU. 18.8 percent of the patients were admitted in the hospital. 20.5 percent of the patients died. 18.8 percent were discharged and 6.3 percent shifted to the HDU. Conclusion: As the results show liver enzyme ALT, D-dimer and bilirubin show significant derangement in COVID-19 patients. This concludes that some, but not all, of the liver enzyme derangement is prevalent in COVID-19 patients. The patients with both diabetes mellitus and hypertension showed highest association with COVID-19. The patients being shifted to the ICU was the highest prognosis of disease. Other than that a large number of patients died, some were admitted to the hospital due to worsening condition, some discharged and others shifted to the HDU. Keywords: Deranged liver enzymes, Liver enzymes, COVID-19, Patients, Prevalence, Association, Prognosis, Outcome.